BLUE GIANTS IN GALACTIC LONGITUDES 270 TO 330 - GONZALEZ, G; GONZALEZ, G (Observatorio Astrofísico de Tonantzintla, Pue, Pue, Mex, 1955)
A catalogue of 150 bright OB stars classified on objective prism plates, taken with the Tonantzintla Schmidt camera, between l=270° and 330° and b=+10° to -10° is presented.
BOL OBS TONAN TACUB
Keywords: BLUE, GIANTS, GALACTIC, LONGITUDES; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS